Total Information in Multivariate Data from Dual Scaling Perspectives - Nishisato, Shizuhiko (Alberta Journal of Educational Research, 2003)
It is an established matter that the total information in multivariate data is defined as the sum of eigenvalues of the variance-covariance matrix. In this article I challenge this time-honored tradition and look at another definition of the total information in data from a dual scaling perspective. This proposal is a step toward unifying the concept of information for both discrete and continuous variables.